Aplikasi Natural Deep Eutectic Solvent (NADES) sebagai Green Solvent pada Ekstraksi Kafein dan Katekin dari Limbah Kulit Kopi - Fitria Puspita; Isna Nurhidayati; Bella Mellisani; Fajar Amelia Rachmawati Putri; Anton Restu Prihadi (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2023)
Various studies have been conducted to support green industry by developing green solvents to replace organic solvents that are generally toxic, volatile, and harmful to human health and the environment. Environmentally friendly solvents that have been successfully developed in the 21st century are eutectic solvents and natural deep eutectic solvents (NADES). NADES can be formed from primary metabolites such as amino acids, organic acids, sugars, or choline derivatives, and has a high ability to extract polar, non-polar compounds, and several other secondary metabolites. The amount of waste generated from the process of separating coffee from its seeds is abundant but has not been used optimally. Coffee husk waste has the potential to be used as a food product because it contains many active substances, especially phenolic compounds such as caffeine and catechins. In this study, an NADES solvent based on choline chloride-proline (1:1) was successfully synthesized and used to extract phenolic compounds from coffee husk waste in the form of caffeine and catechins. The results of the HPLC analysis showed that the levels of caffeine and catechins extracted were 14.5 ppm and 61 ppm, respectively. Based on these results, caffeine and catechins in coffee skin waste were successfully extracted using NADES based on choline chloride – proline (1:1).